Subclinical diagnosis of Caseous lymphadenitis based on Elisa in Sheep from Brazil - Ribeiro, Dayana; Dorella, Fernanda Alves; Pacheco, Luis Gustavo Carvalho; Seyffert, Núbia; Castro, Thiago Luiz de Paula; Portela, Ricardo Wagner Dias; Meyer, Roberto; Miyoshi, Anderson; Luvizotto, Maria Cecília Rui [UNESP]; Azevedo, Vasco (OMICS International, 2013)
Caseous lymphadenitis (CLA), caused by Corynebacterium pseudotuberculosis, is a chronic contagious disease that affects small ruminants and still remains an important problem for many lamb-producing countries. Animals are considered clinically infected when occurs abscesses in superficial lymph nodes. Visceral or internal form can coexist which no apparent clinical signs of infection are seen. The best procedure to avoid spread of the disease is elimination of infected animals. However, as the chronic and subclinical nature of the infection of CLA alternative methods are required for detection and screening. In this study, we described the performance of indirect Enzyme-Linked Immunosorbent Assay (ELISA) for diagnosis of CLA in asymptomatics sheep. Also, test culture and biochemical identification were achieved to confirm CLA infection. The serological diagnostic was performed in sheep symptomatics (n=50) and asymptomatics (n=374) from nine flocks. Analysis reported high positivity of 71% for ELISA in 85% of asymptomatic animal for CLA with a sensitivity of 88% and specificity of 31%. Results from ELISA test in asymptomatic animals against culture for caseous lymphadenitis were more specific (97%) and permitted to exclude healthy animals without symptoms. This study concluded that C. pseudotuberculosis infection could be widely disseminated in sheep flocks in Northwestern region of the state of São Paulo, Brazil and only one screening test is not enough. The association with indirect ELISA test and culture could better indicate the real problem of CLA in sheep flocks.
Keywords: Caseous Lymphadenitis; Corynebacterium pseudotuberculosis; Subclinical diagnostic; Elisa